2016
DOI: 10.1016/j.jtcvs.2016.02.072
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes of infective endocarditis among intravenous drug users

Abstract: The proportion of IVDUs among surgically treated IE patients is increasing. Although IVDUs have lower operative risk, long-term outcomes are compromised by reinfection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
136
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(146 citation statements)
references
References 33 publications
9
136
1
Order By: Relevance
“…In the combined IIA and splenic group, survival was less but this may reflect a more extensive disease process. Although we did not find any difference between outcome of IVDAs and non‐IVDAs, it was reported that IVDAs are at high risk of reinfection and late mortality . The IVDA patients may have pulmonary emboli, leading to a higher rate of morbidity .…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In the combined IIA and splenic group, survival was less but this may reflect a more extensive disease process. Although we did not find any difference between outcome of IVDAs and non‐IVDAs, it was reported that IVDAs are at high risk of reinfection and late mortality . The IVDA patients may have pulmonary emboli, leading to a higher rate of morbidity .…”
Section: Discussioncontrasting
confidence: 66%
“…Although we did not find any difference between outcome of IVDAs and non-IVDAs, it was reported that IVDAs are at high risk of reinfection and late mortality. 43 The IVDA patients may have pulmonary emboli, leading to a higher rate of morbidity. 44 Moreover, IVDAs are at higher risk of human immunodeficiency virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…We also focused our analysis on the impact of referral to addiction services on survival. Optimization of treatment strategies in this population is important given the increasing frequency of injection drug use, 18,19,20 hospitalizations related to injection drug use, 8,21,22 and injection drug use–associated IE. 7,12 …”
Section: Discussionmentioning
confidence: 99%
“…2,[5][6][7] Patients admitted with IDU-associated infections have long lengths of stay, high rates of leaving against medical advice (AMA), readmission, and mortality. [8][9][10][11][12][13] In a British cohort (median age 36 years), five-year mortality after an episode of IDU-associated endocarditis was 42%. 14 Admissions for IDU-associated infections can be a troubling experience for both patients and providers alike.…”
mentioning
confidence: 99%